Mathematical analysis of random phenomena: proceedings of the international conference, Hammamet, Tunisia, 12-17 September 2005 - Cruzeiro, Ana Bela; Ouerdiane, Habib; Obata, Nobuaki (World Scientific, 2007)
This volume highlights recent developments of stochastic analysis with a wide spectrum of applications, including stochastic differential equations, stochastic geometry, and nonlinear partial differential equations. While modern stochastic analysis may appear to be an abstract mixture of classical analysis and probability theory, this book shows that, in fact, it can provide versatile tools useful in many areas of applied mathematics where the phenomena being described are random. The geometrical aspects of stochastic analysis, often regarded as the most promising for applications, are special